Protecting the African child in a changing climate: are our existing safeguards adequate? (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT: This paper sets out the ways in which children in Africa are vulnerable to the consequences of climate change, highlighting where relevant the specific vulnerability of the girl child. It identifies vulnerabilities in access to education, nutrition, the rights of migrants and refugees and the right to participate in decision-making processes. The paper considers these vulnerabilities in the context of the African Charter on the Rights and Welfare of the Child (African Children’s Rights Charter) and the Protocol to the African Charter on the Rights of Women in Africa (African Women’s Rights Protocol), and also looks at specific best practices in attempting to determine the extent to which the African human rights system currently provides adequate protection to children and complies with the best interest of the child principle. It concludes by finding that the African human rights system, particularly when the African Women’s Rights Protocol is read in conjunction with the Children’s Charter, largely provides adequate legal protection to the African child in a climate change context, but identifies room for improvement both in the right to sustainable development and the implementation of the rights as stipulated in the respective instruments, as it relates to climate change induced vulnerability. TITRE ET RÉSUMÉ EN FRANÇAIS: Protéger l’enfant africain dans un climat changeant: les moyens de protection existants sont-ils adéquats? RÉSUMÉ: Cet article expose les façons dont les enfants en Afrique sont vulnérables aux conséquences du changement climatique en soulignant, lorsque cela est nécessaire, la vulnérabilité spécifique des filles. Il identifie les vulnérabilités dans l’accès à l’éducation, la nutrition, les droits des migrants et des réfugiés et le droit de participer aux processus de prise de décision. L’article examine ces vulnérabilités dans le contexte de la Charte africaine des droits de l’enfant et du Protocole relatif aux droits des femmes en Afrique, et examine également les meilleures pratiques spécifiques pour déterminer dans quelle mesure le système africain des droits de l’homme offre actuellement une protection adéquate aux enfants en prenant en consideration le principe de l’intérêt supérieur de l’enfant. Il conclut en constatant que le système africain des droits de l’homme, en particulier lorsque le Protocole relatif aux droits des femmes en Afrique est lu conjointement avec la Charte des enfants, fournit une protection juridique adéquate à l’enfant africain dans un contexte de changements climatiques mais identifie des possiblités d’amélioration dans le contexte du droit au développement durable et à la mise en œuvre des droits tels que stipulés dans ces instruments respectifs, en ce qui concerne la vulnérabilité induite par le changement climatique.
Keywords: African Charter on the Rights and Welfare of the Child; climate change; children; rights; Africa; best interest of the child